If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+1+2X+X+2=63
We move all terms to the left:
X+1+2X+X+2-(63)=0
We add all the numbers together, and all the variables
4X-60=0
We move all terms containing X to the left, all other terms to the right
4X=60
X=60/4
X=15
| 4x+10=-20-x | | −6k+1=−2+7k | | 5a-8=2-(4-3a) | | 8+3D=4d-2 | | (15x-10)=(6x+25) | | 2x+5=2x+5=3x+10 | | 3n+9=-2n+24 | | -2x=-4x2+12 | | -20-20-14g=6g+20 | | (1/x)+(1/2)=7/10 | | m-14=24 | | 5x+2=3x+0 | | 4w+9=19 | | 4x^2-2x-15=0 | | .05x=210000 | | 10k+2=6k+2 | | -30=f/5 | | -10u=-10-9u | | x-3=-11+3x | | 13x+2=4x+30 | | 42=m-6 | | 4x+6=7(3x-7) | | (1/2)200t2=3,600 | | -2x+4=x+10 | | –7=–1+–3z | | -30=f/ | | 14-12b=-14b-16 | | 2.2x-12.7=4.9 | | 4u+30=8u-37 | | -2-3n=-6-7n | | 7x-12=2x+48 | | 5^-3x-30=27 |